Influencia del sellado dentinario inmediato en la fuerza adhesiva de restauraciones indirectas. Revisión de la literatura. - Yánez Flores, Lizeth Katherine (2025)
This literature review examines the influence of immediate dentin sealing (IDS) on the bond strength of indirect dental restorations by analyzing existing scientific literature. The review was conducted using the PRISMA methodology, which is widely applied in systematic literature reviews. The evaluated studies indicate that IDS contributes to greater bond strength compared to the conventional technique (delayed dentin sealing, DDS), primarily due to the formation of a more uniform hybrid layer and the reduction of marginal microleakage. However, the effectiveness of IDS may vary depending on the adhesive system used, the protocol used, particularly the polymerization time, and, finally, the type of cement used for final luting. In conclusion, IDS represents a promising technique that enhances the clinical outcomes of indirect restorations, but its implementation requires a detailed understanding of the appropriate materials and protocols. Future research should focus on standardizing procedures and evaluating their efficacy through long-term clinical studies.